Low antithrombin activity before delivery predicts subsequent hypertensive disorders in pregnancy. Issue 3 (11th October 2019) - Morikawa, Mamoru; Umazume, Takeshi; Nakagawa, Kinuko; Chiba, Kentaro; Kawaguchi, Satoshi; Watari, Hidemichi
Abstract: Objective: To examine whether laboratory parameters can predict the onset of recurrent hypertensive disorders of pregnancy (HDP). Methods: A retrospective study of 257 women with consecutive deliveries at a hospital in Sapporo, Japan, between 2009 and 2017. Women were divided into four groups according to whether or not they had HDP in the first and second peripartum periods (HDP‐HPD, HDP‐Non, Non‐HDP, Non‐Non). HDP was defined as gestational hypertension and/or proteinuria. Laboratory parameters measured on the day of or 1 day before delivery were compared between peripartum‐1 and peripartum‐2. Results: Frequency of HDP in peripartum‐2 was higher among the 24 (9.3%) women with HPD in peripartum‐1 (6/24, 25.0%) than among the 233 (90.7%) women without (3/233, 1.3%) ( P <0.001). In peripartum‐1, women with HDP had lower median antithrombin activity than those without (74% vs 89%, P =0.021). Antithrombin activity in peripartum‐1 was also lower in the HDP‐HDP (67%) than in the HDP‐Non (79%) group ( P =0.021). Antithrombin activities of 77% or less at the first delivery predicted HDP in peripartum‐1 ( P <0.001) and 70% or less predicted HDP in peripartum‐2 ( P =0.018). Conclusion: Women with HDP in peripartum‐1 had a higher incidence of HDP recurrence. Low antithrombin before a first delivery might predict recurrent HDP in a second pregnancy. Abstract : Low antithrombin activity before the first delivery was found to be a predictor of recurrent hypertension disorders of pregnancy in the second peripartum period.